Electronic properties of TaAs2 topological semimetal investigated by transport and ARPES. (23rd March 2022) - Wadge, Ashutosh S; Grabecki, Grzegorz; Autieri, Carmine; Kowalski, Bogdan J; Iwanowski, Przemysław; Cuono, Giuseppe; Islam, M F; Canali, C M; Dybko, Krzysztof; Hruban, Andrzej; Łusakowski, Andrzej; Wojciechowski, Tomasz; et al.
Abstract: We have performed electron transport and angle-resolved photo-emission spectroscopy (ARPES) measurements on single crystals of transition metal dipnictide TaAs2 cleaved along the ( 2 ¯ 01) surface which has the lowest cleavage energy. A Fourier transform of the Shubnikov–de Haas oscillations shows four different peaks whose angular dependence was studied with respect to the angle between magnetic field and the [ 2 ¯ 01] direction. The results indicate elliptical shape of the Fermi surface cross-sections. Additionally, a mobility spectrum analysis was carried out, which also reveals at least four types of carriers contributing to the conductance (two kinds of electrons and two kinds of holes). ARPES spectra were taken on freshly cleaved ( 2 ¯ 01) surface and it was found that bulk states pockets at constant energy surface are elliptical, which confirms the magnetotransport angle dependent studies. First-principles calculations support the interpretation of the experimental results. The theoretical calculations better reproduce the ARPES data if the theoretical Fermi level (FL) is increased, which is due to a small n-doping of the samples. This shifts the FL closer to the Dirac point, allowing investigating the physics of the Dirac and Weyl points, making this compound a platform for the investigation of the Dirac and Weyl points in three-dimensional materials.